Muzy w intymnym świetle. O przemianach w sztuce Odwilży i Października - Hendrykowski, Marek (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2010)
The study assesses the changing nature of the Polish art in the period of liberalization after Stalin’s death. It includes detailed analysis of various (social, political, philosophical and especially aesthetic) implications for important issues such as: poetry, drama, cinema, peinture, sculpture, song, popular culture etc. Marek Hendrykowski provides case studies that lead to alternative ways of viewing current conceptual frameworks of aesthetics and its consequences for interdisciplinary reflexion on arts.
Keywords: history of modern art; aesthetics; poetics; Polish art of the 1950s.; sculpture